2018
DOI: 10.1111/pace.13401
|View full text |Cite
|
Sign up to set email alerts
|

Distinct impacts of heart rate and right atrial‐pacing on left atrial mechanical activation and optimal AV delay in CRT

Abstract: BackgroundControversy exists regarding how atrial activation mode and heart rate affect optimal atrioventricular (AV) delay in cardiac resynchronization therapy. We studied these questions using high‐reproducibility hemodynamic and echocardiographic measurements.MethodsTwenty patients were hemodynamically optimized using noninvasive beat‐to‐beat blood pressure at rest (62 ± 11 beats/min), during exercise (80 ± 6 beats/min), and at three atrially paced rates: 5, 25, and 45 beats/min above rest, denoted as Apace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The RASL is a measure of the delay with which the device senses the atrial depolarization front through the atrial lead, compared to the beginning of its propagation from the sinus node (P wave onset on surface ECG). 21 , 28 In this way, an increased RASL could stand for an increased distance from the sinus node to the RA appendage and thus the RASL should be interpreted as a surrogate of RA enlargement. This delay is not negligible, as in our population it was on average 40 ms, therefore it should be taken into account for sAVD programming.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The RASL is a measure of the delay with which the device senses the atrial depolarization front through the atrial lead, compared to the beginning of its propagation from the sinus node (P wave onset on surface ECG). 21 , 28 In this way, an increased RASL could stand for an increased distance from the sinus node to the RA appendage and thus the RASL should be interpreted as a surrogate of RA enlargement. This delay is not negligible, as in our population it was on average 40 ms, therefore it should be taken into account for sAVD programming.…”
Section: Discussionmentioning
confidence: 99%
“…In all our patients the RA lead was placed in the appendage and all patients were in SR. The RASL is a measure of the delay with which the device senses the atrial depolarization front through the atrial lead, compared to the beginning of its propagation from the sinus node (P wave onset on surface ECG) 21 , 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Kyriacou et al also studied the effect of heart rate on timing of left atrial contraction showing that elevating heart rate by exercise shorted IACT; thus, causing an early LA activation 9 . On the other hand, this phenomenon was not observed whether heart rate was artificially increased by atrial pacing.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kyriacou et al also studied the effect of heart rate on timing of left atrial contraction showing that elevating heart rate by exercise shorted IACT; thus, causing an early LA activation. 9 On the other hand, this phenomenon was not observed whether heart rate was artificially increased by atrial pacing. These findings suggested that the optimization of dynamic AV delay in CRT device should be set differently according to the atrial rhythm as the sensed-paced discrepancy could tend to increase at higher heart rates.…”
Section: The Role Of Iact For Av Delay Optimizationmentioning
confidence: 99%